TEACHER TRAINING AND MULTICULTURAL PEDAGOGY: PROFESSIONAL PEDAGOGICAL KNOWLEDGE, SKILLS, AND ATTITUDES FOR EFFECTIVE TEACHING OF CULTURALLY DIVERSE LEARNERS (Konferensiyalar | Conferences, 2024)
This paper explores the critical role of teacher training in equipping educators with the necessary knowledge, skills, and attitudes for effective teaching in today's multicultural classrooms. The growing diversity of student populations necessitates a shift towards multicultural pedagogy, an approach that values and integrates the cultural backgrounds of learners. The article discusses the core elements of professional pedagogical knowledge for multicultural education, focusing on cultural awareness, understanding learning styles, and utilizing culturally responsive teaching methods. It further emphasizes the importance of developing specific skills, such as fostering inclusive classroom environments, promoting intercultural communication, and addressing issues of equity and social justice. Finally, the article highlights the significance of cultivating positive attitudes towards cultural diversity, including self-reflection, empathy, and a commitment to lifelong learning.